2012
DOI: 10.2514/1.j051407
|View full text |Cite
|
Sign up to set email alerts
|

Geometrically Nonlinear Stress Recovery in Composite Laminates

Abstract: Composite laminates are increasingly being used as primary load bearing members in structures. However, because of the directional dependence of the properties of composite materials, additional failure modes appear that are absent in homogeneous, isotropic materials. Therefore, a stress analysis of a composite laminate is not complete without an accurate representation of the transverse (out-of-plane) stresses.Stress recovery is a common method to estimate the transverse stresses from a plate or shell analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Chaudhuri and Seide [46] rather than using the 3-D equations of equilibrium used 1-D quadratic shape functions through the thickness of each layer to compute transverse shear stress distributions in the laminate. Engelstad et al [47], Byun and Kapania [48] and Hartman et al [49] extended the use of one-step SRSs to geometrically non-linear problems while Park et al [50] used a two-step SRS similar to that employed by Noor et al [43] to predict interlaminar stresses in the laminated panels undergoing finite rotations.…”
Section: Introductionmentioning
confidence: 99%
“…Chaudhuri and Seide [46] rather than using the 3-D equations of equilibrium used 1-D quadratic shape functions through the thickness of each layer to compute transverse shear stress distributions in the laminate. Engelstad et al [47], Byun and Kapania [48] and Hartman et al [49] extended the use of one-step SRSs to geometrically non-linear problems while Park et al [50] used a two-step SRS similar to that employed by Noor et al [43] to predict interlaminar stresses in the laminated panels undergoing finite rotations.…”
Section: Introductionmentioning
confidence: 99%
“…They first approximate a transverse stress field, whose error is reduced via minimisation of a least square functional at the element level. Later, Hartman et al [39] proposed an iterative stress recovery technique with application to laminated plates, which is then extended to include inertial effects in a later publication [42]. These works demonstrated considerable savings in the computational time for accurate interlaminar stresses.…”
Section: D Cauchy Stress Tracking In a Thick Laminated Roofmentioning
confidence: 99%
“…In these instances, it is necessary to use models that output accurate 3D stresses directly from the get-go. Firstly, the 3D stress accuracy of the VKCS model is validated with a simple benchmark from Hartman et al [39], as shown in Figure 7. It shall be noted that the benchmarks for nonlinear Cauchy stresses are scarce in the literature, and mostly focus on laminated flat plates [39][40][41][42] that are 2D in nature (plane stress/strain).…”
Section: D Cauchy Stress Tracking In a Thick Laminated Roofmentioning
confidence: 99%
“…Details on the discrepancy are presented in the appendix of the first author's dissertation. 13 total of 16 elements through the thickness of the laminate.…”
Section: Iiib2 Finite Element Benchmark 3d Solutionmentioning
confidence: 99%